Isolation of vibrio parahaemolyticus from raw vegetables in local markets at Kuching and Samarahan - Ling, Mee Huong (Universiti Malaysia Sarawak (UNIMAS), 2009)
Currently, Vibrio parahaemolyticus are considered as one of the main cause for bacterial gastroenteristis worldwide. Various researches had been conducted and stated that the outbreaks involving raw fruits and vegetables occurred besides those of animal and seafood originated products. This study aims to detect and identify the presence of Vibrio parahaemolyticus in raw vegetables found in local wet markets, Kuching, Sarawak. In this study, samplings were conducted from three different stall found from three different wet markets (Stutong, 7th Mile and Samarindah) respectively. Three types of vegetables were bought and sampled, namely cucumber, tomato and water spinach. Enrichment was done in alkaline peptone water (APW). Thiosulfate-citrate-bile salt (TCBS) agar and CHROMagar Vibrio was applied in the methodology in selection of Vibrio parahaemolyticus.The bacteria appeared as green colonies on TCBS agar and purple on CHROMagar Vibrio. The presumptive colonies were then be streaked on nutrient agar and later stored as stock culture. Biochemical tests were performed in order to identify the isolated colonies. Vibrio parahaemolyticus was found in raw vegetables samples obtained from local wet markets but in little quantity (20 occurrences from 270 total samples or 10.7% isolated from TCBS and 9 occurrences from 270 total samples or 3.3% isolated from CHROMagar Vibrio due to the poor hygiene level in the markets as well as improper handling of vegetables and cross-contamination with other food sold in the market.